Strategi Pembelajaran Gerak Dasar Fundamental melalui Permainan Tradisional Boy di Kelas III SDI Loboleke - Monika Lismen Monis; Robertus Lili Bile; Bernabas Wani; Josep Marianus Rewo; Yohanes Bayo Ola Tapo (MAN Insan Cendekia Jambi, 2026)
This study aims to describe the learning strategy of fundamental movement skills through the traditional game boy for third-grade students at SDI Loboleke. The fundamental movement skills examined include locomotor, non-locomotor, and manipulative movements integrated into traditional game activities. The research employed a descriptive qualitative method with third-grade students of SDI Loboleke as the research subjects. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of the traditional game boy as a learning strategy increases students’ participation, enthusiasm, and fundamental movement skills. Furthermore, the learning process becomes more enjoyable, contextual, and aligned with the developmental characteristics of elementary school students. Therefore, the traditional game boy can be used as an alternative learning strategy in physical education to develop students’ fundamental movement skills.